The Depth Beneath, The Height Above - Bordoli, Andrea (Journal of Anthropological Films, 2020)
The Depth Beneath, The Height Above consists in an exploration of the high alpine region of Robiei, southern Switzerland. Conceived as a sensory piece, the film particularly focuses on the existing relationships between the humans, animals, infrastructural and natural elements that compose Robiei's specific landscape. Through a juxtaposition between the aesthetics and activities that takes place above - the continuous stream of water, the movement of animals, the processes of production of cheese - and respectively below the ground level - the mechanisms, machines and technologies involved in the hydroelectric production, as well as the humans interacting with them -, the film seek to grasp the natureculture and multispecies assemblages through which Robiei and many other contemporary Swiss alpine landscape are being produced.